Association between smoking history and optical coherence tomography angiography findings in diabetic patients without diabetic retinopathy. - Dong-Wei Liu; Zeeshan Haq; Daphne Yang; Jay M Stewart (PLoS ONE)
Purpose To investigate any associations between cigarette smoking and retinal microvascular changes in diabetic patients without visible retinopathy. Design Retrospective, cross-sectional study. Participants 1099 eyes from 1099 diabetic patients with no clinical evidence of diabetic retinopathy (DR) were included in this study. Methods Diabetic patients underwent optical coherence tomography angiography (OCTA) scanning at Zuckerberg San Francisco General Hospital and Trauma Center between April 2018 and September 2019. Patient demographic and clinical information was collected. Standard bivariate statistics and multivariate linear regression were performed. Main outcome measures OCTA parameters included metrics related to the foveal avascular zone (FAZ; area, perimeter, circularity), perfusion density (PD; full, center, inner), and vessel length density (VLD; full, center, inner). Results The study population included 750 non-smokers and 349 smokers. FAZ perimeter was the only OCTA parameter that was significantly different between the two groups on uncontrolled analysis (P = 0.033). Multivariate regression analyses revealed significant associations between lower VLD full (β = -0.31, P = 0.048), lower VLD inner (β = -0.35, P = 0.046) and a history of smoking. No significant associations between cigarette smoking and either FAZ or PD were detected. Conclusions Our results suggest that smoking is likely associated with deleterious changes in the retinal microvasculature of patients with a history of diabetes and no visible DR. Based on these findings, diabetic patients with a history of smoking may benefit from higher prioritization in terms of ophthalmic screening.